Glucocorticoid receptor in stromal cells is essential for glucocorticoid-mediated suppression of inflammation in arthritis. Issue 11 (11th July 2018) - Koenen, Mascha; Culemann, Stephan; Vettorazzi, Sabine; Caratti, Giorgio; Frappart, Lucien; Baum, Wolfgang; Krönke, Gerhard; Baschant, Ulrike; Tuckermann, Jan P
Abstract : Background: Glucocorticoid (GC) therapy is frequently used to treat rheumatoid arthritis due to potent anti-inflammatory actions of GCs. Direct actions of GCs on immune cells were suggested to suppress inflammation. Objectives: Define the role of the glucocorticoid receptor (GR) in stromal cells for suppression of inflammatory arthritis. Methods: Bone marrow chimeric mice lacking the GR in the hematopoietic or stromal compartment, respectively, and mice with impaired GR dimerisation (GR dim ) were analysed for their response to dexamethasone (DEX, 1 mg/kg) treatment in serum transfer-induced arthritis (STIA). Joint swelling, cell infiltration (histology), cytokines, cell composition (flow cytometry) and gene expression were analysed and RNASeq of wild type and GR dim primary murine fibroblast-like synoviocytes (FLS) was performed. Results: GR deficiency in immune cells did not impair GC-mediated suppression of STIA. In contrast, mice with GR-deficient or GR dimerisation-impaired stromal cells were resistant to GC treatment, despite efficient suppression of cytokines. Intriguingly, in mice with impaired GR function in the stromal compartment, GCs failed to stimulate non-classical, non-activated macrophages (Ly6C neg, MHCII neg ) and associated anti-inflammatory markers CD163, CD36, AnxA1, MerTK and Axl. Mice with GR deficiency in FLS were partially resistant to GC-induced suppression of STIA. Accordingly, RNASeq analysis of DEX-treated GR dim FLS revealed a distinct gene signature indicating enhanced activity and a failure to reduce macrophage inflammatory protein (Mip)-1α and Mip-1β. Conclusion: We report a novel anti-inflammatory mechanism of GC action that involves GR dimerisation-dependent gene regulation in non-immune stromal cells, presumably FLS. FLS control non-classical, anti-inflammatory polarisation of macrophages that contributes to suppression of inflammation in arthritis.